METODE LATIHAN PASSING SUPPORT DENGAN GAWANG UNTUK MENINGKATKAN KETEPATAN PASSING PADA PERMAINAN SEPAKBOLA - Ahmad Kabiirurrifaa'i (STKIP Muhammadiyah Kuningan, 2021)
Method of passing support training with the goal to improve football passing accuracy. This research was motivated by passing skills in soccer games for SSB Putra Mayana students. The purpose of this study was to determine the effect of passing support with the goal to increase the accuracy of passing. This research is an experimental research. The population in this study were SSB Putra Mayana students, totaling 15 male students. The sampling technique used is total sampling by determining the population as the research sample. The data collection technique used is the pass test. The data analysis technique in this study is the normality test, homogeneity test and hypothesis testing which are used to determine the effect of passing support with the goal to increase the accuracy of passing. From the results of statistical testing with hypothesis testing, the value of t hit (1.238) < t daf (0.05) (28) (1.70) then accept Ho, it means that there is an influence of the passing support training method with the goal on the accuracy of soccer passing on SSB students Mayana's son.